2021
DOI: 10.3390/ijms22031413
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Role of Matrix Metalloproteinases in Neurodegenerative Diseases: Pathophysiological and Therapeutic Perspectives

Abstract: Neurodegeneration is the pathological condition, in which the nervous system or neuron loses its structure, function, or both, leading to progressive degeneration or the death of neurons, and well-defined associations of tissue system, resulting in clinical manifestations. Neuroinflammation has been shown to precede neurodegeneration in several neurodegenerative diseases (NDs). No drug is yet known to delay or treat neurodegeneration. Although the etiology and potential causes of NDs remain widely indefinable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 244 publications
(307 reference statements)
1
56
0
7
Order By: Relevance
“…MMPs can promote BBB breakdown through degradation of tight junction and basal lamina proteins and thereby facilitate leukocyte infiltration [ 282 ]. Augmented MMP expression is a feature of neuroinflammatory and neurodegenerative disorders, including AD, PD and MS [ 307 ]. For instance, monocytes with enhanced MMP-1, -3, -7 and -9 mRNA expression are more frequent in MS compared to control patients [ 308 ].…”
Section: Mechanisms Mediating Obesity-associated Neuroinflammationmentioning
confidence: 99%
“…MMPs can promote BBB breakdown through degradation of tight junction and basal lamina proteins and thereby facilitate leukocyte infiltration [ 282 ]. Augmented MMP expression is a feature of neuroinflammatory and neurodegenerative disorders, including AD, PD and MS [ 307 ]. For instance, monocytes with enhanced MMP-1, -3, -7 and -9 mRNA expression are more frequent in MS compared to control patients [ 308 ].…”
Section: Mechanisms Mediating Obesity-associated Neuroinflammationmentioning
confidence: 99%
“…MPTP is bio transformed into an active toxic metabolite named 1-methyl-4-phenylpyridinium ion (MPP+), which belongs to the family of mitochondrial complex-I suppressors, and is exclusively involved in devastating DArgic nerve cells within the SN [ 106 , 107 ]. The exploration of MPTP as a triggering factor for degeneration within the SN encouraged the postulation that PD might be precipitated by toxic substances present in the environment [ 108 ].…”
Section: Etiology Of Pdmentioning
confidence: 99%
“…It is activated to degrade the extracellular matrix and participates in the pathological processes of many diseases. A previous study has shown that MMP‐3 acts as a conductive molecule in neuronal apoptosis gene expression and inflammatory processes 25 . After infection with Epstein‐Barr virus and varicella zoster virus, MMP‐3 induced a significant upregulation of keratinocyte endothelial cells and cerebral vascular adventitial fibroblasts at the transcriptional level, which promoted cell migration and invasion, as well as aneurysm and stroke 26,27 .…”
Section: Discussionmentioning
confidence: 97%